Can Social Cognitive Theories Help Us Understand Nurses' Use of Electronic Health Records?. Issue 4 (April 2016) - Strudwick, Gillian; Booth, Richard; Mistry, Kartini
Abstract : Electronic health record implementations have accelerated in clinical settings around the world in an effort to improve patient safety and enhance efficiencies related to care delivery. As the largest group of healthcare professionals globally, nurses play an important role in the use of these records and ensuring their benefits are realized. Social cognitive theories such as the Theory of Reasoned Action, Theory of Planned Behaviour, and the Technology Acceptance Model have been developed to explain behavior. Given that variation in nurses' electronic health record utilization may influence the degree to which benefits are realized, the aim of this article is to explore how the use of these social cognitive theories may assist organizations implementing electronic health records to facilitate deeper-level adoption of this type of clinical technology.